Uji Aktivitas Antibakteri Ekstrak Metanol Propolis dari Lebah Kelulut (Heterotrigona itama) terhadap Bakteri Pseudomonas aeruginosa dan Staphylococcus aureus - Dyah Tantri Wulandari; Supomo Supomo; Husnul Warnida (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
One of the causes of infection is influenced by the occurrence of wounds. Treatment of infected wounds using antibiotics. But antibiotics causes resistance. Then another alternative material from natural ingredients is used, is Propolis from Heterotrigona itama bees. This study aims to determine the inhibition, MIC and MBC of Propolis methanol extract with concentrations of 10%,20%30%,40%,50% against Pseudomonas aeruginosa and Staphylococcus aureus. Research uses experimental research with a non-probability sampling technique, purposive sampling. The extraction method uses methanol solvent maceration. Antibacterial test was carried out by disc diffusion method, positive control of 0.1% clindamycin, negative control of DMSO. The independent variable is the concentration of propolis methanol extract and the dependent variable is the inhibition zone formed and the MIC and MBC values. Analyzed statistically using the ANOVA. Propolis methanol extract inhibited Pseudomonas aeruginosa bacteria at concentrations of 10%:7.74mm, 20%:8.05mm, 30%:10.00mm, 40%:10.05mm, 50%:12,25mm, and can inhibit the growth of Staphylococcus aureus bacteria at concentrations of 10%:7,05mm, 20%:8.00mm, 30%:10.20mm, 40%:11.15mm, 50%:12,05mm. MIC and MBC methanol extract of propolis on the bacteria Pseudomonas aeruginosa and Staphylococcus aureus of 100 mg/ml. Statistical test results showed that all concentrations of propolis methanol extract had a significant difference with the positive control of Clindamycin 0.1%.